2006
DOI: 10.1080/01421590600605272
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy students' professional identity on the edge of working life

Abstract: Market expectations of physiotherapists reflect changing demands of health care for client centred, community based management of chronic disease in an ageing population. This study forms a component part of a longitudinal study of students' socialization throughout their education programme examining the outcome of professional identity throughout professional socialization processes. The aim of this study was to explore characteristics of graduating physiotherapy students' professional identity before leavin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 20 publications
4
48
0
1
Order By: Relevance
“…Our results are consistent with the findings of others in the United Kingdom, Sweden, and the United Arab Emirates who, using different qualitative methods, also identified themes of self-confidence, 18,19 communication, [18][19][20] client-centred practice, 18,19,21 Over time, students in Wessel and Larin's study became more comfortable when communicating with their preceptors, a finding that is also reflected in our study. Consistent with their findings, we identified that inter-professional communication can be either positive or negative and that both provide learning opportunities.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results are consistent with the findings of others in the United Kingdom, Sweden, and the United Arab Emirates who, using different qualitative methods, also identified themes of self-confidence, 18,19 communication, [18][19][20] client-centred practice, 18,19,21 Over time, students in Wessel and Larin's study became more comfortable when communicating with their preceptors, a finding that is also reflected in our study. Consistent with their findings, we identified that inter-professional communication can be either positive or negative and that both provide learning opportunities.…”
Section: Discussionsupporting
confidence: 82%
“…We suggest that educators who may want to implement a guided reflection process be aware of the issues and solutions inherent in this exercise, in order to optimize the experiences and outcomes of students. We agree with others 18,21 who have emphasized the need to focus on professional socialization at multiple points in the entry-to-practice curriculum. We believe that the skills students develop through the process of exploring and reflecting on critical learning incidents will be helpful to them as they continue to develop professionally.…”
Section: Future Work and Recommendationsmentioning
confidence: 60%
See 1 more Smart Citation
“…How these views and assumptions of osteopathy were enacted, shaped practitioners' clinical actions, decisions and resulted in different therapeutic approaches to practice (Trede and Higgs, 2008). The findings that there is diversity in how practitioners identify with their profession and their conceptions of being a professional is consistent with research in physiotherapy (Öhman and Hägg, 1998;Richardson et al, 2002;Lindquist et al, 2006). This study found that differences in therapeutic approach led to variation in the focus of participants' interaction with their patients and the cues they generated and interpreted.…”
Section: Discussionsupporting
confidence: 66%
“…Our theoretical model embodied the core values, beliefs, attitudes, unique clinical skills and roles of the physiotherapists within the health care system [23][24][25][26][27]. Specifically, the questions on our Our Professionalism Inventory consisted of three subscales.…”
Section: Figure-1 Fundamental Elements/core Values/attributes Of Promentioning
confidence: 99%